Media Misrepresentation Predisposing Iranian Social Divide - Rachman, Adelia (Journal Of Middle East and Islamic Studies, 2022)
The Islamic Revolution of 1979 brought Iran to be transformed into a new revolutionary theocratic republic. This is in line with the raison d’être of the Iranian constitution, realizing the life of the nation and state based on the noble and universal values of Islam. Meanwhile, the existence of power competition and conflicting conceptions of authority have been reflected in its political constellation. Islam in the realm of this state is not only understood as a religious institution but also a concept of political spirituality. The hijab policy, for example, has become part of Iranian culture ever since and became a political symbol after the government of Shah Pahlavi in 1936 banned the use of the hijab through the Kashf e Hejab decree. In addition, visual observations through various authentic and reliable video recordings and news reports from Iran over the past 5 years are made to examine what is misunderstood by the world about Iran and its people. Therefore, the results of the analysis should be able to explain how media distortion affects Iran’s political decisions. Because politics plays an important role in the expression of public policy. If the policies implemented contain identity politics, then it will have a significant impact on the emergence of social divisions in Iranian society